The Practice of Love Lesbian Sexuality and Perverse Desire - de Lauretis, Teresa (Indiana University Press, 1994)
Between 1970 and now, in conjunction with earlier and contemporaneous social movements, feminism and poststructuralism have made way for the rise of minority discourse and gay and lesbian studies as fields of scholarly and theoretical research. Conceived from the vantage point of the latter, this book returns to Freudian psychoanalysis and semiotics, to the questions of representation, subjectivity, desire, and their relations to social signification and material reality.